Innovative Leadership within the Context of Foreign Models of Managament - Lystopad, Olena (Pedagogical Discourse, 2012)
The role of guidance and management in securing innovative activity of an organization is concretized in the article, foreign models of management are systematized and characterized, key indicators of innovative leadership are determined, possibilities of effective usage of regulations of foreign theory of management in innovative activity of home educational institutions are offered.